ҚОРАҚАЛПОҒИСТОН РЕСПУБЛИКАСИ ҲУДУДЛАРИДА СИЛЛИҚ ҚИЗИЛМИЯ (GLYCYRIHIZAGLABRAL.) ЎСИМЛИГИНИ УРУҒДАН ЭКИБ КЎПАЙТИРИШ ТЕХНОЛОГИЯСИНИ ТАКОМИЛЛАШТИРИШ - Ибрагимов, М.Ю.; Сабирова, М. (SCIENCE and SOCIETY, 2020)
The article deals with the ways of improving the technology of seed reproduction of licorice naked (Glycyrihiza glabra L.)in the region of the Republic of Karakalpakstan.
Keywords: seeds; beans; rootstock cuttings; laboratory germination; field germination; development